Crossroads of Traditional Knowledge and Intellectual Property in India and Thailand (Journal of Intellectual Property Rights (JIPR), 2024)
Traditional knowledge is gaining momentum. The concept came as an inherent one with the grand demand from the global south onbenefit sharing, which is connected with intellectual property. However, traditional knowledge has its own independent standing as well. Biologically rich countries have started taking steps at the national level to strengthen and reap the benefits of traditional knowledge. This has resulted in interesting situations, like the protection of traditional knowledge through intellectual property. The scenario as to the protection of traditional knowledge through intellectual property prevailing in India and Thailand has been discussed in this article to trace the crossroadsbetween intellectual property and traditional knowledge. The paper reviews the said scenario in India and Thailand, and the samemay allow the reader to ascertain the possible juncture and technical gaps.